PENGARUH PENGGUNAAAN MODEL GAME BASED LEARNING DENGAN METODE GAMIFIKASI TERHADAP HASIL BELAJAR IPAS SD - Nurmitasari Nurmitasari; Esti Setia Ningrum; Garda Trinararya Meidi; Khofifatul Fadilah; Triwahyuningsih; Alifah Fauziah Alfadila (LPPM Universitas Cipta Mandiri, 2026)
This study aims to analyze the effect of the Game Based Learning model assisted by gamification on elementary students’ learning outcomes in Natural and Social Sciences (IPAS). A quantitative approach with a one group pretest-posttest experimental design was employed. The sample consisted of 32 fourth-grade students from SD Negeri 1 Pringsewu Barat in the 2025/2026 academic year. The test instruments were validated and tested for reliability prior to use. The normality test using the Liliefors method indicated that the data were normally distributed (Lcount < Ltable). The t-test results showed that tcount > ttable at a 5% significance level, indicating a significant difference between the students’ average learning outcomes and the Minimum Mastery Criteria (KKM). The findings reveal that applying gamification through interactive media such as Bamboozle enhances students’ motivation, participation, and conceptual understanding, thereby positively influencing their IPAS learning outcomes.